International Appraisal of Nursing Culture and Curricula: A Qualitative Study of Erasmus Students - Jose Siles Gonzalez; Carmen Solano Ruiz; Angela Gaban Gutierrez (Scientifica)
Introduction. Globalization of knowledge has emphasized the need to promote the adoption of international exchange programs in nursing. Nevertheless, the differences in cultural, educational, and structural schemes have challenged the mutual appraisal and understanding of the nursing curricula between countries. Research on nursing curricula should allow performing an analysis of different cultural idiosyncrasies in which educational and health institutions are found. These studies would contribute valuable information to the educative and organizational systems and their cultural variability. Objective. To examine the experiences of nursing students on international exchange programs. Methods. Comparative Education was taken as theoretical background. The clinical practice diaries of seven Spanish Nursing Erasmus students (a European international exchange program) were used as field journals. These students undertook their placements in the United Kingdom. A content analysis was carried out to find major themes. Results. Data extracted from the students clinical practice diaries indicated cultural, educational, and structural differences between countries. Most students reflected the hidden curriculum in their diaries, writing about affective, ideological, personal, and social elements and beliefs. Conclusions. The students’ experiences on international exchange programs were found to be sources of interest to clarify the ideological and cultural connections that underlie educational and health systems.